2020
DOI: 10.1155/2020/8852227
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Water and Lithology on the Deformation and Failure of an Anaclinal Rock Slope in a Hydropower Reservoir

Abstract: A series of settlement, cracking, and collapse of the Zhengjiaping slope has been increasingly developing since October 2015 during impoundment at the Dagangshan Hydropower Station. It is a dangerous signal, which means thatlandslide potential will be existed for the Zhengjiaping slope and poses greatthreat to the operation of hydropower station and traffic safety. Related slope protection measures and research studies have been implemented accordingly in the Zhengjiaping slope to prevent and control adverse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Most current research focuses on observation projects, such as urban railway control network designs [14,15], landslide warnings [16][17][18][19], high fill settlements [20][21][22], ground deformation [23][24][25], and crustal movement [26][27][28][29], achieving good technical results. Fewer studies have addressed GNSS ground deformation along subway lines and GNSS technology is affected by errors, such as satellite ephemeris, tropospheric delay, and multipath effect errors.…”
Section: Introductionmentioning
confidence: 99%
“…Most current research focuses on observation projects, such as urban railway control network designs [14,15], landslide warnings [16][17][18][19], high fill settlements [20][21][22], ground deformation [23][24][25], and crustal movement [26][27][28][29], achieving good technical results. Fewer studies have addressed GNSS ground deformation along subway lines and GNSS technology is affected by errors, such as satellite ephemeris, tropospheric delay, and multipath effect errors.…”
Section: Introductionmentioning
confidence: 99%
“…Toppling, being as a primary failure mode of anti-inclined bedded rock slopes, widely exists in natural and engineering slopes (Chen et al, 2020;Franziska et al, 2019;Gu and Huang, 2016). This failure can be generally divided into three kinds, i.e., flexural toppling, blocky toppling and block-flexure toppling (Goodman and Bray, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have carried out a series of research on slope stability analysis. Cai [6], Wang [7], and Chen [8] collected information on the geological structure, material properties, and macroscopic deformation of a landslide by means of exploration, drilling, and Global Navigation Satellite System. ey used the limit equilibrium method and finite element strength subtraction to research slope stability and found that water storage and rainstorm are closely related to landslide deformation.…”
Section: Introductionmentioning
confidence: 99%